Tackling Carbapenem Resistance and the Imperative for One Health Strategies-Insights from the Portuguese Perspective - Inês Mó; Gabriela Jorge da Silva (MDPI AG, 2024)
Carbapenemases, a class of enzymes specialized in the hydrolysis of carbapenems, represent a significant threat to global public health. These enzymes are classified into different Ambler's classes based on their active sites, categorized into classes A, D, and B. Among the most prevalent types are IMI/NMC-A, KPC, VIM, IMP, and OXA-48, commonly associated with pathogenic species such as Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa. The emergence and dissemination of carbapenemase-producing bacteria have raised substantial concerns due to their ability to infect humans and animals (both companion and food-producing) and their presence in environmental reservoirs. Adopting a holistic One Health approach, concerted efforts have been directed toward devising comprehensive strategies to mitigate the impact of antimicrobial resistance dissemination. This entails collaborative interventions, highlighting proactive measures by global organizations like the World Health Organization, the Center for Disease Control and Prevention, and the Food and Agriculture Organization. By synthesizing the evolving landscape of carbapenemase epidemiology in Portugal and tracing the trajectory from initial isolated cases to contemporary reports, this review highlights key factors driving antibiotic resistance, such as antimicrobial use and healthcare practices, and underscores the imperative for sustained vigilance, interdisciplinary collaboration, and innovative interventions to curb the escalating threat posed by antibiotic-resistant pathogens. Finally, it discusses potential alternatives and innovations aimed at tackling carbapenemase-mediated antibiotic resistance, including new therapies, enhanced surveillance, and public awareness campaigns.